The relevance of corporate governance practices for registered charity organizations in Malaysia - Zainon, Saunah; Abdul Majid, Mazlina; Kum Yoke, Soo; Marzuki Amiruddin Othman, Ahmad; Mustafa Kamal, Musmailina (International Journal of Engineering and Technology, 2018)
The aim of this study is to examine whether registered charities in Malaysia have implemented principle-based corporate governance practices similar to those implemented by publicly-listed companies in Malaysia. This study investigates the relevance of corporate governance practices represented by the Malaysian Code of Corporate Governance (MCCG) 2017 on the financial performance of the registered charity organizations as measured by the program efficiency ratio. Panel data for the registered charities over the period 2014-2016 are analyzed using Ordinary Least Squares (OLS) regression. Program efficiency ratio is used as the dependent variable. The results confirm that board size, inclusion of outside directors and volunteers, as well as the presence of large donors in the board are positive and significant. Both organizational size and age are also important as performance determinants. Attention should be given when interpreting and generalizing the results due to the small sample size used, as compared to the whole population, which may have had a bearing on the results. This study offers insights for policy makers and regulators interested in adopting corporate governance practices for the charity organizations within Malaysia.Â
Keywords: Charity Organizations; Corporate Governance Practices; Performance; Program Efficiency.